Investigating virtual water content and physical and economic water productivity indicators in crops (Case study: Moghan irrigation network, Ardabil province) - Karamat Akhavan Giglou; Milad Kheiry; Hedieh Ahmadpari; Salim Abbasi; Farhoud Kalateh (مدل‌سازی و مدیریت آب و خاک, 2023)
Introduction Agriculture has played a vital role in the economy, life, and culture in the civil history of Iranians. In recent years, this sector is the largest consumer of freshwater resources in this country. One of the adaptive ways to deal with the water shortage is the optimal use of water. In the production process of a commodity, different sources of water may be used, and the type of water supply source can play a significant role in the analysis of virtual water trade. In the period of 2016-2018, previous research covered by the Moghan irrigation network has been conducted in the field of physical and economic water productivity indicators estimation of crops. Moreover, in previous studies, only benefit per drop (BPD) and net benefit per drop (NBPD) indices have been used to estimate the economic productivity of agricultural water. Therefore, in this research, the agricultural year 2020-2021 was studied in order to investigate the physical and economical water productivity indicators of crops covered by the Moghan irrigation network.   Materials and Methods The Moghan Plain is located in the northwestern part of Iran, on the west side of the Caspian Sea, and north of Ardabil province, on the border between Iran and the Republic of Azerbaijan. The total area of the Moghan watershed is more than 5545 km2. The altitude of the region is 50 to 600 m above sea level and its climate is semi-arid and moderate. Most of the agricultural farm covered by Moghan's irrigation and drainage network is devoted to cultivating crops such as wheat, barley, seed corn, fodder corn, soybean, rapeseed, rice, tomato, cotton, sugar beet, and peanut. In this research, these products' virtual water content and physical and economic water productivity are investigated. In this research, to complete the previous studies in the aforementioned field, the virtual water content of the studied products has also been investigated. In addition to the BPD and NBPD, the unit virtual water value (UWV) has been studied to further investigate the Moghan irrigation network economic efficiency of water crops.   Results and Discussion The content of gray, blue, green, and white virtual water of the studied crops, sugar beet, tomato, and fodder corn, have the lowest content of gray virtual water among crops. Among the studied crops, fodder corn, tomato, and sugar beet products, respectively, have the highest physical water productivity, and rice, soybean, cotton, and peanut respectively have the lowest physical water productivity. Regarding gross value index per unit of irrigation volume among the studied crops tomatoes, peanuts, fodder corn, barley, and wheat, respectively have the; highest, moreover peanut, tomato, cotton, fodder corn, and sugar beet products, respectively, have the highest net value index per unit of irrigation volume among the studied crops, however, barley, wheat, rice, and grain corn, respectively, have the lowest net value index per unit of irrigation volume among the studied crops. In addition, tomatoes, peanuts, fodder corn, wheat, and barley have the highest index of value per virtual water unit among the studied crops, respectively, while rice has the lowest value index per virtual water unit among the studied crops. According to the BPD index, tomatoes, peanuts, fodder corn, barley, and wheat are the first to fifth priorities for cultivation in the Moghan Plain. The first to fifth priorities for cultivation in the Moghan plain according to the NBPD index are peanuts, tomatoes, cotton, fodder corn, and sugar beet, and based on the UWV index, tomatoes, peanuts, fodder corn, wheat, and barley are the first to fifth priorities.   Conclusion In the current research, the content of virtual water and the amount of physical and economic water productivity of crops covered by the Moghan irrigation network were calculated. The crop per drop (CPD) index of rice shows the last level in the crop year 2020-2021 due to the amount of water consumed and the significant cost. Also, in the analysis of the BPD and NBPD index, this product has the lowest and ninth priority, respectively, and in the current water shortage conditions in the Moghan Plain, there is a need to review the cultivation of this product. Tomatoes and fodder corn have good productivity in all three indices of CPD, BPD, and NBPD in the crop year 2020-2021. In fact, while tomato does not have a low water requirement, measuring the performance of this product shows the high net and gross profit obtained according to the cost of planting and harvesting. The amount of UWV index of wheat, rapeseed, soybean, rice, fodder corn, seed corn, tomato, barley, sugar beet, cotton, and peanut products is 24269, 15644, 18894, 9956, 36279, 17362, 50073, 23010, 21748, 19403, and 45718 rials per m3, respectively. The proposed approaches and models of this research are different depending on whether the index of physical productivity or economic productivity of water is considered in planning and policy-making.